2010
DOI: 10.1074/jbc.m109.022046
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed Mutagenesis of Apolipoprotein CII to Probe the Role of Its Secondary Structure for Activation of Lipoprotein Lipase

Abstract: Apolipoprotein CII (apoCII) is a necessary activator for lipoprotein lipase (LPL). We had identified four residues (Tyr-63, Ile-66, Asp-69, and Gln-70), presumably contained in an ␣-helix, as a potential binding site for LPL. We have now used structure prediction, mutagenesis, and functional assays to explore the functional role of the secondary structure in this part of apoCII. First, mutants were generated by replacements with proline residues to disturb the helical structure. Activation by mutant G65P was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…In In addition, depending on their plasma concentrations, exchangeable apolipoproteins could absorb to the lipoprotein surface and increase surface pressure to such a degree that the lower-affi nity apolipoproteins are displaced ( 19,51 ). The two lipid-binding, class A, amphipathic ␣ -helices of apoC-II have similar hydrophobicity and length as those of apoC-I, but they differ in helical propensity and number of charged residues, such that apoC-I has a higher predicted lipoprotein affi nity than apoC-II ( 11,20 ). Notably, apoC-II is an activator of lipoprotein lipase and an important regulator of lipoprotein metabolism ( 11,20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In In addition, depending on their plasma concentrations, exchangeable apolipoproteins could absorb to the lipoprotein surface and increase surface pressure to such a degree that the lower-affi nity apolipoproteins are displaced ( 19,51 ). The two lipid-binding, class A, amphipathic ␣ -helices of apoC-II have similar hydrophobicity and length as those of apoC-I, but they differ in helical propensity and number of charged residues, such that apoC-I has a higher predicted lipoprotein affi nity than apoC-II ( 11,20 ). Notably, apoC-II is an activator of lipoprotein lipase and an important regulator of lipoprotein metabolism ( 11,20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The two lipid-binding, class A, amphipathic ␣ -helices of apoC-II have similar hydrophobicity and length as those of apoC-I, but they differ in helical propensity and number of charged residues, such that apoC-I has a higher predicted lipoprotein affi nity than apoC-II ( 11,20 ). Notably, apoC-II is an activator of lipoprotein lipase and an important regulator of lipoprotein metabolism ( 11,20 ). We speculate that apoC-I could bind TAG-rich lipoproteins and increase local surface pressure above the retention pressure of apoC-II, thereby displacing apoC-II from the surface and inhibiting the catabolism of these lipoproteins by lipoprotein lipase.…”
Section: Discussionmentioning
confidence: 99%
“…Without apo-CII, LPL is able to bind to lipoproteins, but catalytic activity is minimal (Olivecrona and Beisiegel 1997). Sequences within the C-terminal portion of apo-CII are essential for its interaction with LPL (Shen et al 2010). Sequences within the N-terminal portion of LPL have been implicated in apo-CII binding (Davis et al 1992), but C-terminal sequences also could play a role (Hill et al 1998).…”
Section: Lplmentioning
confidence: 99%
“…Four residues (Tyr-63, Ile-66, Asp-69, and Gln-70) located on the same face of the C-terminal helix and exposed to solvent in NMR structures form a binding site for LPL (19,24,25). In vitro LPL activity assays showed that replacement of any of these four residues with alanine decreases the affinity of apoC-II for LPL and the catalytic activity of the LPL⅐apoC-II complex (24).…”
Section: Human Apolipoprotein C-ii (Apoc-ii)mentioning
confidence: 99%